2015
DOI: 10.1111/cea.12571
|View full text |Cite
|
Sign up to set email alerts
|

What makes an allergen?

Abstract: SummaryAllergic diseases are an immune disorder reacting to certain type of allergen(s). Remarkably only a small number of proteins of the plant and animal proteome act as allergens. Therefore, allergens have been clustered according to their common structural, biochemical and functional features. Evidence has accumulated that some allergens possess intrinsic adjuvant properties to stimulate the innate immunity. The adjuvant properties appear to contribute to the allergenicity of the respective proteins, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 95 publications
1
56
0
2
Order By: Relevance
“…To execute their role, BMDCs are equipped with a full array of specialized receptors, including pattern‐recognition receptors (PRRs) such as toll‐like receptors (TLRs), C‐type lectins (CTLs), and SRs. Literature suggests that some allergens interact with PRR and thereby stimulate innate and adaptive responses . Considering their role in recognizing glycated products, we selectively blocked SRs and RAGE and found that SRs were responsible for the uptake of both native and glycated BLG.…”
Section: Discussionmentioning
confidence: 96%
“…To execute their role, BMDCs are equipped with a full array of specialized receptors, including pattern‐recognition receptors (PRRs) such as toll‐like receptors (TLRs), C‐type lectins (CTLs), and SRs. Literature suggests that some allergens interact with PRR and thereby stimulate innate and adaptive responses . Considering their role in recognizing glycated products, we selectively blocked SRs and RAGE and found that SRs were responsible for the uptake of both native and glycated BLG.…”
Section: Discussionmentioning
confidence: 96%
“…8,84,103,105109 Prominent examples are major allergens of birch pollen (Bet v 1), timothy grass pollen (Phl p 1), ragweed ( Ambrosia , Amb a 1), molds ( Alternaria alternata , Alt a 1, Cladosporium herbarum , Cla h 1, Aspergillus fumigatus , Asp f 1), and dust mites (Der p 1). 4,139,140 Besides allergens, also adjuvants and their interaction with the immune system play a critical role in the development of allergies.…”
Section: Abundance and Release Of Allergens And Adjuvantsmentioning
confidence: 99%
“…Various signaling pathways, characterized by the secretion of IL‐25, IL‐33, and the activation of different innate immune cells, contribute to generate a pro‐T‐helper 2 environment in the lungs. This ultimately leads to the activation of nonprotective allergen‐specific cells predominantly secreting characteristic Th2 cytokines such as IL‐4, IL‐5, and IL‐13 . These cytokines induce IgE production, cause eosinophilia, stimulate mast cells, promote leukocytosis, and provoke airway hyper reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…This ultimately leads to the activation of nonprotective allergen-specific cells predominantly secreting characteristic Th2 cytokines such as IL-4, IL-5, and IL-13. 10,11 These cytokines induce IgE production, cause eosinophilia, stimulate mast cells, promote leukocytosis, and provoke airway hyper reactivity. This immune activation in asthma patients leads to repeated attacks of breathlessness, cough, and wheeze occurring secondary to broncho-constriction in the setting of airway hyper-responsiveness, mucus hyper-secretion, and airway remodeling.…”
mentioning
confidence: 99%